Alpha-1 Antitrypsin as a Regulatory Protease Inhibitor Modulating Inflammation and Shaping the Tumor Microenvironment in Cancer - Siyu Xiang; Liu Yang; Yun He; Feng Ding; Shuangying Qiao; Zonghua Su; Zheng Chen; Aiping Lu; Fangfei Li (Cells)
Alpha-1 antitrypsin (AAT) is a key serine protease inhibitor for regulating proteases such as neutrophil elastase. AAT restrains the pulmonary matrix from enzymatic degradation, and a deficiency in AAT leads to inflammatory tissue damage in the lungs, resulting in chronic obstructive pulmonary disease. Due to the crucial biological function of AAT, the emerging research interest in this protein has shifted to its role in cancer-associated inflammation and the dynamics of the tumor microenvironment. However, the lack of comprehensive reviews in this field hinders our understanding of AAT as an essential immune modulator with great potential in cancer immunotherapy. Therefore, in this review, we have elucidated the pivotal roles of AAT in inflammation and the tumor microenvironment, including the structure and molecular properties of AAT, its molecular functions in the regulation of the inflammatory response and tumor microenvironment, and its clinical implications in cancer including its diagnosis, prognosis, and therapeutic intervention. This review seeks to bridge the gap in the understanding of AAT between inflammatory diseases and cancer, and to foster deeper investigations into its translational potential in cancer immunotherapy in the future.